Counter movement e squat jump: análise metodológica e dados normativos em atletas - Rodrigues, M. E.; Marins, J. C. B. (Revista Brasileira de Ciência e Movimento, 2011)
Different sports modalities use the explosive force with vertical component as a determinant of performance and among these, football, volleyball and basketball stand out. The potency of the lower limbs is required in these specific modalities where the level of strength generated can be the differential in the athlete's performance. Thereby, the counter movement jump and squat jump are the usual control procedures for coaches, athletic trainers and physiotherapists to determine the athlete's physical capacity, to measure the result of a training program, and as a functional measure of an athlete preparation to return to sport after an injury. This study collected information from the available literature about the main methodological aspects involved in the measurement of the explosive strength of lower limbs using the counter movement jump and squat jump, identifying the aspects related to validity, reliability, objectivity, indications for several sports, methodological recommendations for its application and possible errors. Thus, it offers to the reader a survey of studies to compose a database with reference values in different sports modalities.